Chester Barnard revisited: spontaneous orders and the firm. Issue 6 (December 2019) - Walsh, Aidan; Brady, Malcolm
Abstract: That governance within the firm is deliberate, conscious and hierarchical, based on authority is considered almost axiomatic. Chester Barnard is cited as an early theorist of this view. In this short article we review Barnard's original theory of authority, his later work and his private correspondence with F. A. Hayek, Michael Polanyi, Bertrand de Jouvenal and others. We show that Barnard focused in his later thinking less on authority and more on 'responsibility' and on the spontaneous nature of coordination within the firm, argued for 'invisible hand' explanations of coordination within the firm and compared coordination within the firm to market coordination. We use this information to produce novel insights into the work of Chester Barnard and also to demonstrate that his insights into the inner workings of firms is still not completely understood or reflected in the literature on the firm.